Evaluation of Panbio rapid antigen test for SARS‐CoV‐2 in symptomatic patients and their contacts: a multicenter study - Ireri Thirion-Romero (Elsevier, 2021)
Background: Point-of-care rapid tests to identify SARS-CoV-2 can have clinical benefits. Methods: A cross-sectional study in adults visiting emergency services or screening sites of referral hospitals for COVID-19 to validate the diagnostic performance of a rapid antigen test for SARS-CoV-2 (Abbott's Panbio) compared with reverse transcription-polymerase chain reaction (RT-PCR) testing. Tests were performed by health personnel in a routine situation during a COVID-19 outbreak. Results: A total of 1060 participants (mean age 47, 46% with a self-reported comorbidity) were recruited from 8 hospitals in Mexico. Participants provided 1060 valid Panbio rapid test-RT-PCR test pairs with 45% testing positive in the RT-PCR. Overall sensitivity of the Panbio test was 54.2% (95% CI 51%–57%), and 69.1% (95% CI 66%–73%) for patients during the first week of symptoms. Sensitivity depended on viral load (cycle threshold (Ct) of RT-PCR) and days of symptoms. With a Ct ≤25, sensitivity was 82% (95% CI, 76%–87%). Specificity of the Panbio test was >97.8% in all groups. Conclusions: The Panbio rapid antigen test for SARS-CoV-2 had good specificity but low sensitivity. A negative test requires confirmation with RT-PCR, especially for testing after the first week of symptoms.